Operational procedures of Kansas feedyards - L. Koons; Jack G. Riley (Kansas Agricultural Experiment Station Research Reports, 1977)
Twenty-four Kansas feedyards with 432,000 head capacity participated in a survey on operation procedures. The survey covered five areas: processing, animal health, rations, facilities, and marketing. Methods differed most in processing and starter-ration ingredients.
Keywords: Report of progress (Kansas State University. Agricultural Experiment Station); 291; Cattlemen& #x27; s Day; 1977; Beef; Feedyards; Processings; Rations